COVID-19 as a potential trigger for refractory arrhythmias and electrical storm in a patient with dilated cardiomyopathy: a case report - A. M. Osadchy; I. A. Makarov; A. V. Skoptsova; L. B. Mitrofanova; A. V. Kamenev; S. G. Shcherbak; D. S. Lebedev (Российский кардиологический журнал)
Arrhythmias occur both in the acute coronavirus disease 2019 (COVID-19) and in the post-acute period, which may be associated with the long-term SARS-CoV-2 persistence. In a case report, patient with primary dilated cardiomyopathy, an implanted cardioverter-defibrillator, recurrent ventricular arrhythmias, and an electrical storm are presented. The patient was repeatedly hospitalized in a city hospital, where electrical cardioversion, antiarrhythmic therapy, radiofrequency ablation of recurrent ventricular tachycardia regions, including emergency ("lifesaving") combined catheter radiofrequency destruction of the electrical storm substrate, was performed. Subsequently, against the background of ongoing postoperative therapy, massive pulmonary embolism (PE) suddenly developed, which led to the death. Autopsy established that the cause of the patient’s death was massive pulmonary embolism; SARS-CoV-2 and enterovirus was detected in the myocardium. Based on an autopsy study, the patient was diagnosed with primary dilated cardiomyopathy with secondary active chronic lymphocytic myocarditis.